2022
DOI: 10.1097/fjc.0000000000001315
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin Alleviates LPS-Induced H9C2 Cell Injury by Inducing Mitochondrial Autophagy

Abstract: Sepsis leads to the damage of multiple organs, and thereby adversely affects the cardiovascular system. At present, no effective method has been found to treat myocardial injury caused by sepsis. Although Puerarin was reported to attenuate lipopolysaccharide (LPS)-induced mitochondrial injury in H9C2 cells, the effects of Puerarin in sepsis-induced myocardial injury remain unclear. In this study, H9C2 cells were stimulated with LPS, CCK-8 assays were performed to assess cell viability, and flow cytometry and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…When energy deficiency, nutrient deprivation, and inflammation occur, the energy-sensitive AMPKα1 and AMPKα2 genes can be activated [ 42 ]. A previous study indicated that the level of ATP, ADP, and AMP in myocardiocytes decreased after LPS induction [ 43 ]. In the present study, the energy-deficient state of the duodenum, cecum, and liver was induced by the LPS, stimulating an increase in AMPKα1 and AMPKα2 mRNA and protein expression, whereas quercetin significantly decreased this expression.…”
Section: Discussionmentioning
confidence: 99%
“…When energy deficiency, nutrient deprivation, and inflammation occur, the energy-sensitive AMPKα1 and AMPKα2 genes can be activated [ 42 ]. A previous study indicated that the level of ATP, ADP, and AMP in myocardiocytes decreased after LPS induction [ 43 ]. In the present study, the energy-deficient state of the duodenum, cecum, and liver was induced by the LPS, stimulating an increase in AMPKα1 and AMPKα2 mRNA and protein expression, whereas quercetin significantly decreased this expression.…”
Section: Discussionmentioning
confidence: 99%